Principles of security and trust : 5th International Conference, POST 2016, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2016, Eindhoven, the Netherlands, April 2-8, 2016, Proceedings /: 5th International Conference, POST 2016, held as part of the European Joint Conferences on Theory and Practice of Software, ETAPS 2016, Eindhoven, the Netherlands, April 2-8, 2016, Proceedings. (2016) - Unknown
No abstract available